SYNTACTIC LEVEL MODELS USED FOR THE EXPRESSION OF COMMUNICATIVE INTENTION OF SUPPORT IN THE ENGLISH LANGUAGE - Матвеева, Н.А.; Жасубиева, А.С. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2014)
The article is devoted to the topic of linguistic means of expression of communicative intention of support in the works of English-speaking authors. The article discusses the concepts of "intention", "communicative intention", "communicative intention of support"; the types of communicative intention of support (psychological support, support-consent, support in the action, support-approval) in accordance with the speech acts in which it is reflected in the dialogic discourse are given; the syntactic level models used to express communicative intention of support in the works of British and American writers are studied and described.
Keywords: intention; communicative intention; intention of support; syntactic models of expression of support intention